Production Of Novel Recombinant Antipfhrp2 VNAR-G1 Protein Using Escherichia Coli Bl21(DE3) Expression System - Kok, Boon Hui (Universiti Sains Malaysia, 2020)
Malaria rapid diagnostic tests (RDTs) act as important antibody-based immunoassays for prompt malaria diagnosis. Conventional monoclonal antibodies (mAbs) are widely used in RDTs but it can be easily degraded at high ambient temperatures. Hence, the shark VNARS might be good alternatives to mAbs due to its higher thermal stability and binding affinity with antigens. In this study, the recombinant anti- PfHRP2 VNAR-G1 protein was produced in E. coli expression system through various steps such as recombinant cell isolation, PCR, agarose gel electrophoresis, plasmid extraction, transformation and protein expression. Besides, the combinatorial effects of temperature and IPTG concentration towards the cell density of recombinant BL21(DE3) based on the absorbance readings and cell wet weights were investigated using software R. Based on the statistical analysis of 2-way ANOVA and multivariable regression, both expression variables had highly significant combined interactions (p < 0.05) towards absorbance readings and cell wet weights. There was significant and strong positive correlation between IPTG concentrations and absorbance readings (p < 0.05, r = 0.9512). The presence of recombinant anti- PfHRP2 VNAR-G1 protein with a molecular size of about 12 kDa was detected and confirmed through SDS-PAGE and western blot analysis. The protein concentration was determined as 0.209 mg/mL from 0.406 g of crude cell extract. In conclusion, all the objectives in this study were achieved and the recombinant sdAb from shark VNAR specific for PfHRP2 binding was successfully produced in E. coli BL21(DE3) as the expression host.